Correlação dos níveis séricos e dos polimorfismos nos genes de citocinas (TNF-α, INF-γ, TGF-β1 e IL-10) com a apresentação clínica da hepatite B crônica - CONDE, Simone Regina Souza da Silva (Universidade Federal do Pará, 2014)
Chronic hepatitis B has a wide spectrum of clinical manifestations resulting from various factors, such as the pattern of secretion and polymorphism in cytokine genes. This work aims to correlate the TNF-α -308G/A, INF-γ +874A/T, TGF-β1 -509C/T e IL-10 -1081A/G polymorphisms and serum levels of these cytokines with the clinical presentation of hepatitis B. It was selected 53 consecutive cases of hepatitis B divided into group A (inactive carrier= 30) and B (chronic hepatitis / cirrhosis= 23). As a control, we selected 100 individuals anti-HBc and anti-HBs positives. Serum levels of cytokines were determined by enzyme immunoassays (eBiosceince, Inc. California, San Diego, USA). The gene amplification of cytokines was carried out by PCR and histopathological analysis followed by METAVIR classification. It was identified that genotype TNF-α -308GA was more prevalent among B group than controls and that presence of A allele increased the risk for chronic disease (OR= 2,6). The serum levels of INF-γ and IL-10 were higher (p <0,001) in controls than others groups A and B and the TGF-β1 levels were lower (p < 0,01) in controls. It was noted that inflammatory activity > 2 correlated with higher levels of TNF-α and IFN-γ (p<0.01) and fibrosis > 2 with higher levels of INF-γ (p <0.01). In the studied population, lower INF-γ and IL-10 levels and higher TGF-β1 level were associated with chronic hepatitis B, and that the presence TNF-α -308 A allele increased in 2,6 the risk for chronic disease .